Impulse - Gould, Steven (Tom Doherty Associates, LLC, 2013)
Cent, the daughter of a man brutally pursued by the government and other dangerous adversaries for his ability to teleport, triggers an avalanche while illegally snowboarding and discovers her own teleporting abilities.